Generic Asymptotic Expansions. - Van der Hoeven, Joris
We give an expansion algorithm for germs of exp-log functions at infinity which is correct modulo Schanuels conjecture. We also show how the algorithm can be made generic. More precisely, we reduce the expansion algorithm for exp-log functions depending on parameters to the problem of deciding whether a given system of exp-log equations and inequalities in several variables admits a solution.
Keywords: Asymptotic expansion; Exp-log function; Algorithm; Genericity